Promotion and Education on The Prevention of Juvenile Delinquency From a Health Perspective for Youth Members of Youth Organizations Karang Taruna - Gusgus Ghraha Ramdhanie; Bambang Aditya Nugraha (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Adolescence is a transitional phase from childhood to adulthood. Adolescence needs to be accompanied in such a way because adolescents are still looking for their identity. Drinking alcohol and smoking are considered commonplace behaviors for adolescents, whereas in fact, if this is not properly supervised, it will be very prone to falling into juvenile delinquency. Based on the results of the study, problems that occur in adolescents were identified, namely the high smoking behavior and consumption of alcohol in adolescents. As an effort to overcome these problems, promotional and educational activities related to